2008
DOI: 10.1111/j.1365-2265.2007.03150.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of iodine on the reference interval of TSH and the optimal interval of TSH: results of a follow‐up study in areas with different iodine intakes

Abstract: Iodine nutrition is an important factor associated with TSH concentration even in the rigorously selected reference population. Baseline TSH of 1.0-1.9 mIU/l is an optimal interval with the lowest incidence of abnormal TSH in 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 27 publications
7
69
2
2
Order By: Relevance
“…Even excluding patients with high thyroid antibodies, serum TSH concentration is an independent risk factor of DTC, suggesting the increasing risk of DTC in patients with TSH in the upper end of normal or markedly elevated level is unlikely to be solely due to increased antithyroid antibody levels. This demonstrates the real association between TSH and malignancy, given the well known influence of anti-thyroid antibodies on TSH [21,22]. Moreover, our data show that higher TSH in patients with DTC occurs independent of age, which is also an important influencing factor on serum TSH levels.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Even excluding patients with high thyroid antibodies, serum TSH concentration is an independent risk factor of DTC, suggesting the increasing risk of DTC in patients with TSH in the upper end of normal or markedly elevated level is unlikely to be solely due to increased antithyroid antibody levels. This demonstrates the real association between TSH and malignancy, given the well known influence of anti-thyroid antibodies on TSH [21,22]. Moreover, our data show that higher TSH in patients with DTC occurs independent of age, which is also an important influencing factor on serum TSH levels.…”
Section: Discussionmentioning
confidence: 51%
“…The sensitivity of TSH assay was 0.01 mIU/L. The reference range, intra-assay and inter-assay coefficients of variation were 0.3-4.8 mIU/L [21], 4.9% and 5.2%, respectively, for TSH. Serum TPOAb exceeding a level of 50 KIU/L and/or TgAb exceeding a level of 40 KIU/L were considered as high serum autoantibody values [22].…”
Section: Thyroid Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of the TPOAb and TgAb measurements is 10 IU/L. Serum TPOAb exceeding a level of 50 IU/L and /or TgAb exceeding a level of 40 IU/L were considered as positive [2].…”
Section: Thyroid Functionmentioning
confidence: 99%
“…erence range should be narrower [1,2]. A large-scale epidemiological survey reported that "greater than 95% of healthy euthyroid subjects have a serum TSH concentration <2.5μIU/mL [3].…”
mentioning
confidence: 99%